Explicit deposit insurance and bank risk-taking: Does banking supervision matter? - Raheel Mumtaz; Imran Abbas Jadoon; Nadeem Sohail (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study explores the influence of supervisory powers and structure of a banking supervisor on the bank's risk-taking caused by the implementation of explicit deposit insurance (EDI). We explorethe data of publically traded 1,936 banks of 96 countries, from the Bank scope during 2002 to 2015. Using the Hierarchical Linear Modeling (HLM), findings revealedthat banking supervisionreducesthe moral hazard of bank's risk-taking in non-crisis affected countries, either allocated supervisory powers are low or high. Additionally, conferring the greater supervisory authority to banking supervisor strengthened the financial health of banks amongst both crisis and non-crisis affected countries. Furthermore, centralbank working as a banking supervisor with greater supervisory powers seemed to mitigate the moral hazard of bank's risk-taking. While central bank's low supervisory powers have little or no impact to controllingthe bank risk-taking. Hence, the allocation of greater supervisory powers to a central bank heightens the investors and depositors' confidence inthe depository financial institutions.
Keywords: 330; official supervisory powers; supervision structure; deposit insurance; bank risk-taking; moral hazard